Daulatabad neighborhood: A home to be in the world - P. Mohammadi; N. Amiri; S. Gholipour (Taḥqīqāt-i Farhangī-i Īrān)
The perception of residents of a neighborhood about their life there may indicate "restlessness" and "tension" or "peacefulness" and "calmness". The starting point of the present study is the lived experience of one of the authors and the exploratory observation of two others in the Daulatabad neighborhood of the city of Kermanshah who found that the general feeling of the residents there is related to "place" and their sense of belonging. As such, the article intends to search as what makes the residents to feel so. While searching for the main question, the accuracy of more or less intuitive statement was also tested. But the emphasis had been to find elements that make life in Daulatabad more or less acceptable to its inhabitants. The theoretical basis is a narrative view and specifically the micro concept of Boje’s narrative. Through interviews, observation and of course data of the lived experience, two important elements in the life of neighborhood residents were highlighted and the two meanings that showed the acceptability of the neighborhood for its residents are: Local mosque and bazaar, symbols of religion and the world. But what has made these two bodies important in creating a sense of belonging to the neighborhood is how they are interwoven in daily life and of course, the placement of dimensions of these symbols in the collective memory. The present article, in fact, describes and analyzes these facts.